Indian stamp act - Basu, M.N. (New Delhi, 2007)
This is being a full-fledged commentary on the Indian Stamp Act and related laws, incorporating Central and state amendments in Acts, Rules, Reductions, Remissions etc., and Tables, Case-law.
Keywords: Stamp act-India